Kesesuaian Operasional Produk Asuransi Syariah dengan Fatwa DSN MUI No:21/DSN-MUI/X/2001 (Studi Kasus AJB Bumiputera 1912 Cabang Surabaya) - Hidayat, Rian Rahmat; Zaki, Irham (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
Sharia insurance in Indonesia has experienced a fairly rapid development since theÂ promulgation of MUI fatwa number:21/DSN-MUI/X/2001 about sharia insurance. However,Â that is still questionable is does the sharia insurance company really run the productÂ operational based on MUI fatwa.This study aims to determine whether product operational of sharia insurance of AJBÂ Bumiputera1912 is in conformity with the sharia rules to follow six indicator akkad, premi,Â claims, investment, reinsurance, and management of the fund from MUI fatwa or not.The research method is used is a case study with a qualitative descriptive approach. TheÂ data used in this study is that the data derived from primary data obtained from fieldworkÂ and secondary data derived from the literature and a wide range of written document. ThisÂ study using data derived from the management of sharia insurance AJB Bumiputera 1912 inÂ the branch of Surabaya and sharia insurance participants of AJB Bumiputera 1912.The results of this research is operational products of sharia insurance of AJB BumiputeraÂ 1912 were in accordance with Indonesian Ulama Council fatwa DSN Number:21/DSNMUI/X/2001. The suitability reflected from the existence of akkad tabarruâ and akkad tijarahÂ as investment funds (mudharabah), management of premium funds based on sharia, claimsÂ fund based on first contract, investment made in accordance with the mandate ofÂ participants, then reinsurance process done only to sharia-based reinsurance company.